Multiscale computational evaluation of Vitex trifolia phytochemicals as VEGFR2 inhibitors for targeted breast cancer therapy - Arooj Fatima; Muhammad Umer Khan; Saooda Ibrahim; Iqra Khurram; Qasim Ammar; Raima Rehman; Alaa S. Alhegaili; Raghad S. Alhejaili; Nawal Alsubaie; Muhammad Ikram Ullah (PLoS ONE, 2025)
Breast cancer (BC), the second most common cancer, is a genetically heterogeneous disease driven by angiogenesis, cell growth, metastasis, and oxidative stress. VEGFR2, a key angiogenesis regulator, presents a potential target for inhibiting the angiogenic process essential for tumor growth. The present study aimed to investigate the therapeutic potential of phytochemicals of Vitex trifolia to inhibit VEGFR2 for BC. The current study employed extensively in silico-based computational tools to assess the binding affinity and interactions through docking and validating through simulations, along with evaluating the molecular characteristics of the phytochemicals of Vitex trifolia. The docking results revealed that VT-6 (cynaroside) showed the highest docking score (−14.611 kcal/mol), followed by VT-10 (−13.641 kcal/mol) against the VEGFR2 protein. Significant stable interactions were formed by the key interacting residues of the binding pocket (GLU917, ASP1046, LYS868, CYS919, and GLU885), also highlighted through the SIFT analysis. Additionally, the density functional theory (DFT) analysis demonstrated balanced electrophilic and nucleophilic electronic distribution and reactivity for VT-6. The simulations further validated the stability of VT-6 within the binding cavity of VEGFR2, exhibiting flexibility within a range of <3Å and stable conformational changes. Moreover, the MM/GBSA calculations also signify that VT-6 exhibited stronger binding affinity with more negative free energies (−32.5 kcal/mol MM/PBSA, −34.7 kcal/mol MM/GBSA). Notably, principal component analysis (PCA) and free energy landscape (FEL) indicated that the VT-6 complex remained compact during 200 ns simulations. Conclusively, these findings underscore VT-6 as a potent VEGFR2 inhibitor against BC. However, optimizing the ADMET profile through structural modifications and nanocarrier delivery, along with in vivo and in vitro experimental validation, will enhance its therapeutic potential.